EFFICIENCY OF DISPOSABLE PETRI DISH WASTE IN MICROBIOLOGY LABORATORY USING THE DMAIC METHOD (DEFINE, MEASURE, ANALYZE, IMPROVE, CONTROL) (Case Study: PT. XYZ) - Khoirudin, Aziz; Arif Gunawan, Ikhsan; Rahman, Taufiq; Nur Endah, Wati; Endah Wahyuni, Ayu (International Journal of Psychosocial Rehabilitation, 2020)
PT. XYZ is one of the pharmaceutical companies in Indonesia which is the largest producer in the domestic market. The company has several departments in supporting the production process including the Microbiology QC (Quality Control) department that plays a role in controlling the quality of raw materials to finished products from microbial contamination, as well as providing certainty that products consistently have quality that is suitable for their intended use. In the process, there are problems in handling disposable petri dish waste in the microbiology laboratory. Most waste was produced from the analysis dish waste of 12,228 pcs/month with a percentage of 65% of the total petri dish waste of 18,920 pcs. Analysis of the causes of the accumulation of disposable petri dish waste is carried out with the DMAIC approach. Based on this approach, it is known that the cause of the problem is the inefficient use of petri dishes so that there is a buildup of waste in the destruction room, so the solution to fix and improves that is to replace one-room petri dishes with two-room petri dishes. In use, the two-room petri dishes is more efficient because it has a bulkhead making it possible to replicate in one cup so that the cost of consumable petri dishes for one space that requires 2 dishes to analyze 1 sample can be decreased. Savings due to the replacement of one-room dishes into two spaces amounted to Rp. 600/sample or 27.5%.